Human Leukocyte Antigen and Interleukin 2, 10 and 12p40 Cytokine Responses to Measles: Is There Evidence of the HLA Effect? - Ovsyannikova, Inna G. (2007)
HLA class I and class II associations were examined in relation to measles virus-specific cytokine responses in 339 healthy children who had received two doses of live attenuated measles vaccine. Multivariate linear regression modeling analysis revealed suggestions of associations between the expression of DPA1*0201 (p=0.03) and DPA1*0202 (p=0.09) alleles and interleukin-2 (IL-2) cytokine production (global p-value 0.06). Importantly, cytokine production and DQB1 allele associations (global p-value 0.04) revealed that the alleles with the strongest association with IL-10 secretion were DQB1*0302 (p=0.02), DQB1*0303 (p=0.07) and DQB1*0502 (p=0.06). Measles-specific IL-10 secretion associations approached significance with DRB1 and DQA1 loci (both global p-values 0.08). Specifically, suggestive associations were found between DRB1*0701 (p=0.07), DRB1*1103 (p=0.06), DRB1*1302 (p=0.08), DRB1*1303 (p=0.06), DQA1*0101 (p=0.08), and DQA1*0201 (p=0.04) alleles and measles-induced IL-10 secretion. Further, suggestive association was observed between specific DQA1*0505 (p=0.002) alleles and measles-specific IL-12p40 secretion (global p-value 0.09) indicating that cytokine responses to measles antigens are predominantly influenced by HLA class II genes. We found no associations between any of the alleles of HLA A, B, and Cw loci and cytokine secretion. These novel findings suggest that HLA class II genes may influence the level of cytokine production in the adaptive immune responses to measles vaccine.